Searching for Virtue in the City: Bell and Her Sisters. (3rd July 2017) - Frederickson, George; Meek, Jack Wayne
Abstract : The hope for virtue in the city is to be found not just in the individual propensity to be virtuous but, more so, in the development of political and organizational rules and procedures, in virtuous leadership, and in the development of a virtuous public culture. This claim is made as a way to view what has come to be known as the Bell scandal—a scandal that fits squarely in the tradition of the municipal reform movement. The article places the scandals in Bell and its neighboring cities in this context and grounds its claims in a framework of municipal reform ethics.